2023
DOI: 10.1126/scitranslmed.abq0476
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific features of the T cell repertoire after allogeneic hematopoietic cell transplantation in human and mouse

Susan DeWolf,
Yuval Elhanati,
Katherine Nichols
et al.

Abstract: T cells are the central drivers of many inflammatory diseases, but the repertoire of tissue-resident T cells at sites of pathology in human organs remains poorly understood. We examined the site-specificity of T cell receptor (TCR) repertoires across tissues (5 to 18 tissues per patient) in prospectively collected autopsies of patients with and without graft-versus-host disease (GVHD), a potentially lethal tissue-targeting complication of allogeneic hematopoietic cell transplantation, and in mouse models of GV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…The latter question has recently been addressed by DeWolf et al in a systematic study of TCR repertoires across multiple different tissue sites. 71 The authors identified anatomically defined TCR repertoires and motifs that only partially overlapped with circulating TCR repertoires, underscoring the importance of the study of tissue-resident memory T cells. Besides providing a deeper understanding of T cells, scRNA-seq studies of tissue biopsies should also investigate the role of other cell types in the pathogenesis of GvHD, such as B cells, for which Poe et al have provided a baseline by defining their transcriptional profiles in peripheral blood and bone marrow.…”
Section: Allogeneic Hsctmentioning
confidence: 98%
“…The latter question has recently been addressed by DeWolf et al in a systematic study of TCR repertoires across multiple different tissue sites. 71 The authors identified anatomically defined TCR repertoires and motifs that only partially overlapped with circulating TCR repertoires, underscoring the importance of the study of tissue-resident memory T cells. Besides providing a deeper understanding of T cells, scRNA-seq studies of tissue biopsies should also investigate the role of other cell types in the pathogenesis of GvHD, such as B cells, for which Poe et al have provided a baseline by defining their transcriptional profiles in peripheral blood and bone marrow.…”
Section: Allogeneic Hsctmentioning
confidence: 98%
“…However, late-phase GVHD is maintained within affected tissues locally by tissue-resident TCF1 + pTex-like cells without migrating between target organs ( 83 ). In patients with multiple sites of GVHD, the dominant T cell receptor repertoires are not consistently observed across tissues within the same patient, raising the possibility that GVHD arose in each local tissue independently ( 84 ). Furthermore, patient-derived resident memory T cells persist for many years after HCT in association with the development of skin GVHD ( 85 ).…”
Section: Separation Of Gvl and Gvhd Through Localized Gvhd Therapymentioning
confidence: 99%